If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(1/2x+1)=(-2+3x)-2(x-2)
We move all terms to the left:
2(1/2x+1)-((-2+3x)-2(x-2))=0
Domain of the equation: 2x+1)!=0We add all the numbers together, and all the variables
x∈R
2(1/2x+1)-((3x-2)-2(x-2))=0
We multiply parentheses
2x-((3x-2)-2(x-2))+2=0
We calculate terms in parentheses: -((3x-2)-2(x-2)), so:We get rid of parentheses
(3x-2)-2(x-2)
We multiply parentheses
(3x-2)-2x+4
We get rid of parentheses
3x-2x-2+4
We add all the numbers together, and all the variables
x+2
Back to the equation:
-(x+2)
2x-x-2+2=0
We add all the numbers together, and all the variables
x=0
| 9+2x3=11x3= | | (x+11)=(5x+1) | | 18x−14=−14 | | -4=2(x-18) | | -3b+5=-31 | | 0.25x-3=-7 | | (8x+16)+(4x+20)=180 | | 1/x=0.11 | | (90-x)+(180-x)=192 | | xx6=84 | | 8h-8=56 | | 8-8b=-24 | | 5x–15=10 | | -9-c=-3c+5 | | -10=1=2p-5 | | i-18=2 | | 7g+5/2=20 | | 6x-30=12+14 | | 2x-47=x+3 | | 4(x-3)-8=-20 | | 2x=3x+1=21 | | 1.4(x+2)=7.5 | | 9+9j=-7+7j | | -1(x+4)=3x+17+3x | | 3(h−4)=8 | | -16+51=-5(x+6) | | 2(5x1)=(3x11+7x | | r-17=-24 | | 4d+14=3(d–1) | | 4k-13=2 | | -3(2x-7)-1=-8-1/2(-8x+10) | | -4+2(5-7x)=-24-8x |